SHORT STAPELIUM TENDON: A RARE CAUSE OF CONDUCTIVE HEARING LOSS - Lutfullaev G.U; Kobilova Sh.Sh; Madaminova N.E; Karimova Z.Kh; Narziev M.M.; Zoyirov O.T (Western European Studies, 2025)
Stapes tendon abnormalities have been reported as a cause of conductive hearing loss; theoretically, such abnormalities limit the motion of the stapes. Objectives: To demonstrate a rare cause of conductive hearing loss caused by a stapes tendon abnormality and to compare the clinical data of this patient with other cases of stapes tendon abnormalities described in the literature. Method: A clinical case of one patient with a short stapes tendon and a review of the Englishlanguage literature on stapes tendon abnormalities. Results: This is a case report of a 13-year-old boy with a shortened stapes tendon causing unilateral hearing loss, accompanied by a literature review. Unlike other reported cases, this patient did not have an ossified tendon, namely an extremely short tendon. The boy recovered normal hearing after excision of the stapes tendon
Keywords: hearing loss; stapes; tendons